Haemorrhagic cerebral air embolism from an atrio-oesophageal fistula following atrial fibrillation ablation. (September 2015) - Koa-Wing, M; Jamil-Copley, S; Ariff, B; Kojodjojo, P; Lim, P B; Whinnett, Z; Rajakulendran, S; Malhotra, P; Lefroy, D; Peters, N S; Davies, D W; Kanagaratnam, P
We report the case of a man found unconscious three weeks following atrial fibrillation (AF) ablation. Cranial and thoracic imaging demonstrated multiple areas of pneumo-embolic infarction secondary to an atrio-oesophageal fistula (AEF). AEF is a recognised, but rare, complication of AF ablation. 1–8 Early recognition is critical as the mortality is 100% without surgical intervention. We consider the postulated mechanisms of AEF formation, the spectrum of clinical presentation, investigations and treatment.